The Evaluation of Pharmacodynamics and Pharmacokinetics of Anti-thrombin DNA Aptamer RA-36 - Zavyalova, Elena; Samoylenkova, Nadezhda; Revishchin, Alexander; Turashev, Askar; Gordeychuk, Ilya; Golovin, Andrey; Kopylov, Alexey; Pavlova, Galina (Frontiers in Pharmacology, 2017)
Anticoagulants are a vital class of drugs, which are applied for short-term surgical procedures, and for long-term treatments for thrombosis prevention in high risk groups. Several anticoagulant drugs are commercially available, but all have intrinsic disadvantages, e.g. bleeding risks, as well as specific ones, e.g. immune response to peptide/protein drugs. Therefore, the search for novel, efficient and safe anticoagulants is essential. Nucleic acid aptamers are an emerging class of contemporary pharmaceuticals which are fully biocompatible and biodegradable; they have low toxicity, and are as efficient as many protein-based drugs. The anti-thrombin DNA aptamer RA-36 has been created using a combination of rational design and molecular dynamics, showing several extra-features over existing aptamers. Aptamer RA-36 has a bimodular structure; the first G-quadruplex binds and inhibits thrombin, whereas the second G-quadruplex varies the properties of the first. This bimodular structure provides a favorable dose-effect dependence allowing the risk of bleeding to be potentially decreased. Here, the results of efficiency trials of the aptamer are presented. The aptamer RA-36 has a distinctive species specificity; therefore, the careful selection of experimental animals was required. The anticoagulant activity was characterized in rats and monkeys in vivo. Antithrombotic activity was evaluated in the live murine model of the induced thrombosis. Pharmacokinetics was estimated by tracking radionuclide labeled aptamer in rats. The aptamer was thoroughly characterized using bivalirudin as a reference drug. Despite the different profiles of anticoagulant activity, these two compounds could refer to each other, and the corresponding doses could be estimated. Bivalirudin turned out to have 10-fold higher anticoagulant and antithrombotic activity. The difference in activity is easy to explain due to the pharmacokinetic profiles of the substances: the aptamer RA-36 has 20-fold faster elimination from blood with a half-life of 1 minute. The entire dataset revealed that the non-modified DNA aptamer could be an alternative to the currently used bivalent peptide inhibitor; the dosage profile could be improved by manipulating aptamer pharmacokinetics. The study has revealed aptamer RA-36 to be one of the most promising candidates for further development as a new generation of anticoagulants.